2020
DOI: 10.1002/hyp.13825
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater–surface water exchange in the intertidal zone detected by hydrologic and coastal oceanographic measurements

Abstract: Groundwater-surface water exchange in the intertidal zone detected by hydrologic and coastal oceanographic measurements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Sous et al (2016) carried out a field experiment on a microtidal beach and revealed the presence of a rather consistent groundwater circulation pattern under the swash zone. Heiss, Michael, and Puleo (2020) demonstrated that the lens of infiltrating seawater that moves downward through the unsaturated zone to the water table, contributing to the formation of the circulation cell, moves landward and seaward as the tide and swash zone move across the beach surface.…”
Section: Introductionmentioning
confidence: 99%
“…Sous et al (2016) carried out a field experiment on a microtidal beach and revealed the presence of a rather consistent groundwater circulation pattern under the swash zone. Heiss, Michael, and Puleo (2020) demonstrated that the lens of infiltrating seawater that moves downward through the unsaturated zone to the water table, contributing to the formation of the circulation cell, moves landward and seaward as the tide and swash zone move across the beach surface.…”
Section: Introductionmentioning
confidence: 99%